A Bird's Eye View of the Malheur Wildlife Refuge Occupation: Nonhuman Agency and Entangled Species. Issue 3 (3rd April 2019) - Dare, Alexa M.; Fletcher, C. Vail
ABSTRACT: In January 2016, armed militants occupied the Malheur National Wildlife Refuge, demanding an end to government control of the Refuge and other similarly protected public lands. Public discourse about the occupation highlights ongoing tensions around land use, property rights, and government overreach. The discourse foregrounds human animal concerns and all but erases nonhuman animal agency. This essay considers nonhuman animal agency and the entanglement of humans, nonhumans, and the land as seen in the occupation and surrounding discourse. We draw from critical animal studies and feminist posthuman theory to examine how discourses of the occupation produce and reinforce a sense of human exceptionalism that elides a more useful and nuanced understanding of human–nonhuman–land relatedness and agency. The analysis shows how, in the case of the Malheur occupation, occupiers and critics alike rely on discourses of "othering" towards both nonhuman animals and other humans. We take a "birding" perspective on the occupation to show how the webs of relationality that connect humans, nonhumans, and the land might be activated as an antidote to destructive discourses of human exceptionalism.